2016
DOI: 10.1021/acs.orglett.6b01395
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Marine Natural Product Solomonamide B Necessitates Stereochemical Revision

Abstract: The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the (1)H and (13)C NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Therefore, in the particular case of the solomonamides, the scarce availability of T. swinhoei clearly conditioned the further characterization of the compounds’ bioactivities. In the last years, different studies toward the synthesis of solomonamides have been reported, mainly by Reddy et al [15,17,37,38,39,40,41]. In fact, very recently, the total syntheses of solomonamides A and B have been reported [13], which led to their stereochemical revision with respect to that initially proposed, and confirmed the anti-inflammatory activities reported for the natural products.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, in the particular case of the solomonamides, the scarce availability of T. swinhoei clearly conditioned the further characterization of the compounds’ bioactivities. In the last years, different studies toward the synthesis of solomonamides have been reported, mainly by Reddy et al [15,17,37,38,39,40,41]. In fact, very recently, the total syntheses of solomonamides A and B have been reported [13], which led to their stereochemical revision with respect to that initially proposed, and confirmed the anti-inflammatory activities reported for the natural products.…”
Section: Discussionmentioning
confidence: 77%
“…To our delight, the macrocycle 37 was crystallized from ethyl acetate‐hexane mixture resulting in suitable crystals for the diffraction. The single crystal X‐ray structure analysis of 37 clearly indicated that three contiguous stereocentres of non‐peptide portion in macrocycle are 2 S , 3 S , 4 S . After conformation of stereochemistry of non‐peptide portion in macrocycle 37 we indirectly confirmed stereochemistry of macrocycle 30 as 2 R , 3 R , 4 R in non‐peptide portion by comparing NMR spectral data of acid 10 and previously reported non‐peptide acid 12 .…”
Section: Resultsmentioning
confidence: 53%
“…Here we are reporting syntheses of all possible stereoisomers of solomonamide B macrocycles particularly around AHMOA fragment keeping the alanine stereocenter fixed. Among these, two macrocycles with 2 S , 3 R , 4 R and 2 S , 3 S , 4 S stereochemistry were previously synthesized in our lab during the stereochemical revision of natural products . Synthesis of the remaining six possible stereoisomers is a challenging task and involves remodelling of the synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…As DFT calculations for structural assignments can sometimes be error-prone [ 10 , 11 , 12 , 13 ], at the outset of this project, we opted for the synthesis of structure of pagoamide A ( 1 ) and one of its diastereomers 1a , where the two serine residues switched positions. The success of this investigation would allow us to further resolve the structure of this natural product.…”
Section: Introductionmentioning
confidence: 99%